Multicase Study of Technician Careers in Manufacturing Industry - Achmad Romadin; Yoto Yoto; Didik Nurhadi (Universitas Ahmad Dahlan Indonesia, 2021)
The development of industrial world every year changes very rapidly. The demand for workforce competence in the industry is increasing. Competence is the ability to do work effectively. The aim of this study is to identify careers in the position of Technician. This study uses a qualitative approach, by using interviews, documentation, and observation. The results of research regarding the work of Technician positions in the industry, include: checking production machines, coordinating and supervising, repairing production machines, and manufacturing spare parts for production machines. There are several competencies in the scope of work that a technician must have, regarding: Measuring Instruments, Technical Drawings, General Machining, and Special Requirements. Incentives obtained are based on grade, and holiday incentives. The salary range earned by the technician position is above the UMK of the area where the industry is located.